A descriptive study to determine the customer satisfaction & current customer relationship status in newly launched products of Banglalink Digital Communications Limited - Sakib, Saadman (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.